Interação genótipo x ambientes e seus efeitos na escolha de localidades para avaliação de linhagens de soja (Glycine max (L.) Merril) - Sussumu Sakiyama, Ney; Sediyama, Tuneo; Sigueyuki Sediyama, Carlos; Silva Reis, Múcio (Revista Ceres, 2025)
Forty-three soybean genotype evaluation trials were conducted at 16 localities (municipalities) in the State of Minas Gerais, in the agricultural years of 1981/82 (21 trials) and 1982/83 (22 trials), to study the efficiency of soybean genotype selection in comparison with the selection made in only two localities, with three planting dates at each locality. It was concluded that improved soybean genotypes may be efficiently selected in two years, with three planting dates and two adequately chosen localities, when compared with 43 trials distributed in 16 localities during two agricultural years.